Data recording, data retrieval and the big data phenomenon: A Quranic perspective - Qadri, Mehran; Maree, Morshed; Noordin, Mohamad Fauzan (IRPN Publishers, 2015)
When we look at the Qur’an (The religious text of the Muslim faith), we find detailed information about every aspect of human life. The Qur’an talks about science, social science, mathematics, psychology, business and many other fields of study. However, in this paper we are going to talk about something we often think has no relation to the Qur’an - modern information technology. If we go through the Qur’an, we can find many verses that relate to various fields of information technology such as security, networks, etc. One such area of information technology is data recording or to use the general term, database. The Qur’an talks about keeping records of various things and the retrieval of that data according to different criteria in many places. So when we think about modern databases, we can actually see that the basic fundamentals of such technology have already been laid down in the Qur’an itself. Therefore, when it comes to the latest phenomenon of ‘Big Data’, it is very much possible to see it from a Quranic perspective as well. The Qur’an, in fact, talks about ‘Big Data’ at a divine scale. This research into the relation between modern data recording, data retrieval, the ‘Big Data’ phenomenon and the Quranic text led us to conclude that the principle ideas behind these modern technologies have already been mentioned in the Qur’an which was revealed over fourteen hundred years ago.